2021
DOI: 10.1093/jeea/jvab019
|View full text |Cite
|
Sign up to set email alerts
|

Wage Equalization and Regional Misallocation: Evidence from Italian and German Provinces

Abstract: Italy and Germany have similar geographical differences in firm productivity – with the North more productive than the South in Italy and the West more productive than the East in Germany – but have adopted different models of wage bargaining. Italy sets wages based on nationwide contracts that allow for limited local wage adjustments, while Germany has moved toward a more flexible system that allows for local bargaining. We find that Italy exhibits limited geographical wage differences in nominal terms and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(8 citation statements)
references
References 42 publications
(22 reference statements)
1
6
0
Order By: Relevance
“…Germany is a significant setting. Unlike other Continental Europe countries, the specific bargaining structure allow nominal wages in Germany to be more dependent on local labor market conditions (Boeri et al (2021)) and this chimes well with the main mechanism of our model. Moreover, in recent years it experienced a boom in the real estate market (a more than 50 % cumulative growth in residential property prices form 2015 to 2022) 7 and robust growth in nominal earnings (2 -3 % average annual change from 2008 to 2019).…”
Section: Introductionsupporting
confidence: 72%
“…Germany is a significant setting. Unlike other Continental Europe countries, the specific bargaining structure allow nominal wages in Germany to be more dependent on local labor market conditions (Boeri et al (2021)) and this chimes well with the main mechanism of our model. Moreover, in recent years it experienced a boom in the real estate market (a more than 50 % cumulative growth in residential property prices form 2015 to 2022) 7 and robust growth in nominal earnings (2 -3 % average annual change from 2008 to 2019).…”
Section: Introductionsupporting
confidence: 72%
“…Second, our paper is close to an extensive literature that has built regional models of growth and development for the South of Italy, which started with the classic work by Chenery (1962). Finally, our work stresses the importance of heterogeneity in regional productivity, which has recently been studied by Boeri et al (2021) in connection with wage policies in Italy and Germany.…”
Section: Introductionmentioning
confidence: 56%
“…8. On the wage rigidity in Italy, see for example (Belloc et al, 2019;Boeri et al, 2021). In France, which has a similar framework to Italy, Bassanini et al (2020) and Marinescu et al (2021) found a limited effect of concentration on wages, while a strong effect on the number of hirings, supporting our idea that in a labour market characterized by high wage rigidity, the employers intervene more through their labour demand rather than their wages.…”
mentioning
confidence: 58%
“…8. On the wage rigidity in Italy, see for example (Belloc et al ., 2019; Boeri et al ., 2021). In France, which has a similar framework to Italy, Bassanini et al .…”
Section: Notesmentioning
confidence: 99%